Study on failure mechanism of roadway with soft rock in deep coal mine and confined concrete support system. (November 2017) - Wang, Q.; Pan, R.; Jiang, B.; Li, S.C.; He, M.C.; Sun, H.B.; Wang, L.; Qin, Q.; Yu, H.C.; Luan, Y.C.
Abstract: Surrounding rock control is a tough issue in roadway with soft rock in deep underground. To solve this problem, the original supporting scheme is monitored and analyzed on site with Liangjia coal mine of China as engineering background. Located in Longkou seashore mining area, Liangjia coal mine is a typical deep mine with soft rock in China. The analysis shows that roadway deformation is large with a big damage range; anchor bolts are generally in seriously broken surrounding rock; the support potential fails to be played; the support strength of arch is insufficient and the post bearing capacity is low. All of these mainly lead to the failure of the roadway bearing capacity. Numerical test is conducted with the consideration of arch strength, geostress, mechanical parameters of surrounding rock and other factors; it is to comparatively analyze the deformation of surrounding rock, the range of plastic zone and the mechanical properties of support components under different factors; therefore, the failure and control mechanism are defined on deep roadway with soft rock; and a concept of "high-strength, integrity, and pressure-relief" is proposed. Meanwhile, a confined concrete (CC) support system is developed; and a laboratory comparative test for full-size arch is carried out on its core component - CC arch and the conventional U36 arch as well. The research shows that the instability and failure of the entire U36 arch is caused by partially bending and buckling of the arch, and its bearing capacity is drastically reduced. The bearing capacity of CC arch is 2.03 times compared with that of U36 arch, and also has a good post bearing capacity. On the basis of these numerical and laboratory tests, a comparative test is carried out on-site. The monitoring results in the test show the rock deformation in CC support testing section is only 22.4% of that in U36 arch support; and no yield and failure phenomenon occurs in CC support test section, which proved the effectiveness of CC support system on surrounding rock control. Highlights: The failure and control mechanism are analyzed on deep roadway with soft rock. A confined concrete support system is developed. A laboratory test for full-size arch is carried out on CC arch and U36 arch. A field test is conducted on CC arch and U36 arch to compare their control effect on surrounding rock.